The Role of The National Land Agency (BPN) In Resolving Land Disputes In Indonesia - Pasamai, Syamsuddin; Salle, Salle (Pelopor Publikasi Akademika, 2024)
Land disputes are one of the complex and frequent agrarian problems in Indonesia. Therefore, systematic and targeted efforts are needed to resolve land disputes in Indonesia. The National Land Agency (BPN) as a government agency tasked with managing land has an important role in resolving land disputes. This research aims to examine the role of BPN in resolving land disputes in Indonesia. The research method used in this study is a qualitative method. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that BPN has a central role in resolving land disputes in Indonesia. As an institution responsible for land administration and management, BPN plays a role in facilitating legal and administrative processes related to ownership, utilization and resolution of land disputes. BPN is tasked with providing legal certainty regarding land status, verifying ownership claims, and providing land certificates to the legal owners. Apart from that, BPN also plays a role in mediating and resolving conflicts between parties involved in land disputes, whether between individuals, traditional communities, or private parties. BPN's role is not only limited to administrative aspects, but also includes efforts to create fair and sustainable solutions, taking into account various social, economic and environmental aspects.